Distribution of fluoride and calcium in plaque biofilms after the use of conventional and low‐fluoride dentifrices. Issue 4 (31st October 2013) - Pessan, Juliano Pelim; Alves, Karina Mirela Ribeiro Pinto; Italiani, Flávia de Moraes; Ramires, Irene; Lauris, José Roberto Pereira; Whitford, Gary Milton; Toumba, Kyriacos Jack; Robinson, Colin; Buzalaf, Marilia Afonso Rabelo
<x xml:space="preserve">Abstract</x> Background The distribution of fluoride and calcium in plaque after the use of fluoride dentifrices has not yet been determined. Aim To evaluate fluoride and calcium distribution in sections of biofilms generated in situ after the use of conventional and low‐fluoride dentifrices. Design Children (n = 11, 8–10 years old) brushed with placebo (fluoride‐free), low‐fluoride (513 mgF/kg), and conventional (1072 mgF/kg) dentifrices twice daily for 1 week, following a double‐blind, cross‐over protocol. Biofilms were generated using Leeds in situ devices, which were collected 1 and 12 h after brushing, and sectioned through their depth. Sections were grouped (10 × 5 μm) for fluoride and calcium analysis. Sections 4 μm thick were used for image analysis and determination of biomass fraction. Results were analysed by anova, Tukey's test, and linear regression analysis (P < 0.05). Results Fluoride and calcium were mostly located at the outer sections of biofilms for all dentifrices tested, and these ions were directly correlated throughout most of biofilm's sections. Results for conventional dentifrice were significantly higher than for the placebo, but did not differ from those for the low‐fluoride dentifrice. Conclusions The use of a low‐fluoride dentifrice did not promote a higher fluoride uptake in inner biofilms' sections, as hypothesized. As plaque fluoride was significantly elevated only after the use of the conventional dentifrice, the recommendation of low‐fluoride formulations should be done with caution, considering both risks and benefits.